ELSABAGH SCORING SYSTEM FOR ASSESSING SEVERITY AND TREATMENT IMPROVEMENT IN MULTIPLE ORAL LICHEN PLANUS - Permatasanti, Ayu; Hapid, M. Hasan; Hidayat, Wahyu (FKG ULM, 2024)
Introduction: Lichen planus (LP) is a mucocutaneous, chronic, autoimmune disease, with various clinical manifestations, often involving the oral mucosa, and commonly occurs in adults 30-60 years old. Among the various scoring systems for oral lichen planus, the Elsabagh scoring system is valid, accurate, relatively easier to teach, relatively faster to master, and does not require complex calculations.Objective: This paper aimed to report and evaluate the successful therapy given based on using the Elsabagh scoring system in oral lichen planus. Case: A 53-years-old woman came to the Department of Oral Medicine with a main complaint of pain in the upper gums and lower right left a year ago. The pain got worse when eating highly spiced and spicy foods. She felt pain when brushing her teeth. Extra oral examination revealed multiple white plaques on the vermilion border. Intra-oral examination revealed erosive, erythema, accompanied by white plaques mesh-like shaped, irregular, and painful, on the upper labial, right and left buccal mucosa, posterior teeth of the mandible that extend into the mucobuccal fold, and gingiva, palate, and posterior gingiva of the right and left maxillae. Amalgam fillings were found on teeth 37 and 46 with plaque and calculus. Based on clinical features, the patient was diagnosed with Multiple Oral Lichen Planus of Erosive and Reticular type. Case management: The patient received topical and systemic corticosteroids, mouthwashes, and supplements. She was advised to stop eating highly spiced and spicy foods, replace amalgam filling with tooth-colored filling, scaling, and replace removable dentures with permanent dentures. The evaluation result using the Elsabagh scoring system showed an improvement from the value of 8 on the initial visit to 3 on the last visit. There was an improvement in the patient's condition after treatment based on evaluation using the Elsabagh scoring system in this case. The Elsabagh scoring system can correlate disease severity with subjective symptoms, allowing comparisons between the initial evaluation of lesions and treatment efficacy or disease progression in oral lichen planus. Keywords: Autoimmune, Elsabagh Scoring System, Oral Lichen Planus